Multinational Activity in a Macroeconomic Model of the Small Open Economy - Alkis Henri Otto (Hamburg Institute of International Economics (HWWA), 2004)
We study the effects of FDI and increasing multinational activity utilizing a macroeconomic two-sector model of the small open economy with flexible exchange rates and perfect capital mobility. The focus is on horizontal greenfield investment and its impact on production, exchange rates, trade, and welfare. In the host country, an increase in multinational activity harms the established industries. Nevertheless it increases welfare. In the home country, an increase in multinational activity lowers domestic output of the established industries too and, thereby, decreases welfare.
Keywords: F21; F41; 330; Foreign Direct Investment; Multinational activity; Welfare effects; Macroeconomic effects; Direktinvestition; Kleines-offenes-Land; Wohlfahrtseffekt; Makroökonomischer Einfluss; Theorie